Implementation of harmonics reduction filters in non-linear equipment at plastic manufacturing company - Muhammad fadlan siregar; Muhammad Ikhwan Fahmi; Syofyan Anwar Syahputra; Habib Satria; Indri Dayana; Moranain Mungkin (Faculty of Engineering, Malikussaleh University, 2024)
Harmonics are produced by non-linear loads such as televisions, computers, microwaves, fluorescent lamps that use electronic ballasts and others. The harmonic content contained in non-linear loads causes the quality of electrical power to become poor and the quality of electrical power to decrease, the greater the use of non-linear loads, it is estimated that the harmonics generated will be greater and can disrupt the system performance of other electronic equipment and can also cause overheating of electrical power sources, plastic manufacturing company measurements, Source Voltage Balanced (V peak) Unbalanced (V peak) 312∠ 00, 311∠ -1200, 312∠ 1200, Phase R 3.23 Ampere, Phase S 3.24 Ampere Phase T 3, 24 Amperes as in figure 2a, and THD Current in Phase R 25%, Phase S 23% Ampere Phase T 24%, the total harmonic distortion was above 5% and the analysis for the single tuned filter was C value > 50.64 μF, L value > 10.093 H, and R value > 50.98 Ω. then after, harmonic values, a filter was installed to reduce the THD value to 1.4% and the overall THD value was below 5% in accordance with IEEE standards.